Design and analysis of active queue management algorithm based on predictive control - WANG Ping; CHEN Hong; LU Xiao-hui (Tongxin xuebao)
Model predictive control as a novel active queue management（AQM） algorithm was proposed for Internet system with large delay,called MPAQM.Considering the causality of time-delay system,the predicted output was defined.Then,the control requirement was converted to the optimal control objective,and the drop probability was obtained by solving the optimal problem.Furthermore,the delay-independent stability condition of closed-loop system was derived,which gave the guidelines how to select the parameters of MPAQM algorithm to assure the stability and fast convergence of the network system.The performances of MPAQM were evaluated through a series of simulations in NS2 under the single/multiple topology.The simulation results show that the queue length with MPAQM algorithm reaches the desired value with minimal tracking error and lower drop probability.MPAQM algorithm outperforms RED,PI and SPI-RED algorithms in terms of disturbance rejection,stability,and robustness.